Juan de Mena, Laberinto de fortuna. Ed. de Maxim P. A. M. Kerkhof. Castalia, Madrid, 1995; 431 pp. (Nueva Biblioteca de Erudición y Crítica, 9). - Santibáñez Escobar, Julia (El Colegio de México, 1996)
Se reseñó el libro: Laberinto de fortuna. Ed. de Maxim P. A. M. Kerkhof.